Inovasi Guru dalam Pembelajaran PAI di Masa Pandemi Menggunakan Model Pembelajaran E-Learning di SMAN 1 Kediri - Yuliana, Eva; Turmudi, Moh. (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
In the era of the Covid-19 pandemic that hit the world in 2020, the face-to-face learning process could not be carried out by all educational institutions in Indonesia. However, the education process must continue to ensure that every Indonesian citizen gets an education. This requires all educational institutions to carry out learning through courage. In this situation the teacher remains innovative in order to get the desired learning, the use of the web or the internet when learning is very important how the teacher is able to master technology and be able to cope. On the basis of this background, the researchers asked the following research questions (1) How are PAI Learning Conditions in a Pandemic Period (2) How PAI Teacher Innovations in E-Learning Learning Models during a Pandemic (3) How is PAI Learning Evaluation in a Pandemic Period. This research is a qualitative research with a case study design. Data collection techniques through participant observation, in-depth interviews, and documentation. Meanwhile, for data analysis researchers use the flow analysis modelwhich covers; data reduction, data display and conclusion drawing. The results of the study are: (1) PAI Learning Conditions during the Pandemic in the form of choosing learning methods, controlling student activity, assessing practical material (2) PAI Teacher Innovation in E-Learning Learning Models in the form of e-learning learning innovations, e-learning supporting media, e-learning support methods (3) Evaluation of PAI Learning in the Pandemic Period evaluation of assessments for teachers, students and assessments in accordance with the RPP.